Crescimento e sobrevivência de Crassostrea gasar no sistema fixo em diferentes níveis na coluna d’agua e sob diferentes densidades de estocagem - PEREIRA JUNIOR, Jucimauro de Araújo (2023)
The optimization of oyster farming systems aims to increase productivity, being necessary to evaluate the growth and survival of the organism to avoid economic damage. Thus, the objective of the present study was to evaluate the growth and survival of the oyster C. gasar in the seed and juvenile phases under different stocking densities in a fixed tabletop system with two floors exposed at different depths of the water column. For this, the system used was the table with the first floor at a distance of 0.39m to the second floor. The experiment was carried out in a 2x2 factorial, with the first factor the floors (1st and 2nd floor) and the second factor the stocking densities in the seed and juvenile phases (seed: D750 and D1000; Juvenile: D250 and D450), the The experimental period was six months for each phase, and the height (mm) and survival (%) were measured monthly. In the seed phase, the monthly growth of oysters at density D1000 was higher at 150 days on both floors in relation to density at D750, equaling at the end of 180 days. For juveniles, the lowest density D250 presented the highest values in height on both floors in relation to oysters with density of D450, reaching heights of 84.69±4.23 and 83.30±5.62mm, respectively. There was no interaction for the growth and survival of oysters in relation to floors and stocking density, however, in the seed phase, it is observed that the lowest density (D750) had the highest survival (92.60±4.54%), not difference in growth in relation to floors and density was observed. In the juvenile phase, no difference was observed in growth and survival to the factors studied. Regarding the growth of oysters with breeding time, height increases with time, reaching 60mm in 180 days for both floors. Emphasizing that the increase in height in the seed phase at the highest density is probably due to a higher mortality rate. Therefore, oyster growth was not influenced by floors and stocking density, however, mortality was higher in the seed phase at density D1000.